A Single Surgeons Experience with Enhanced Recovery after Surgery: An Army of One. Issue 7 (July 2016) - Mosquera, Catalina; Koutlas, Nicholas J.; Fitzgerald, Timothy L.
The benefits of enhanced recovery after surgery (ERAS) have been demonstrated for multiple surgical procedures in high-volume programs. However, resources required for its implementation may be daunting to individual surgeons. Patients undergoing elective abdominal procedures from June 2013 to April 2015 by a surgical oncologist before and after the implementation of an ERAS protocol were reviewed. A total of 179 patients were included. The mean age of the patients was 63 years, and a majority of them were females (53.6%), white (61.5%), had a Charlson score of 0 to 2 (45.8%), and a Clavien complication grade of 0 to I (60.1%). The univariate analysis revealed that the ERAS protocol was associated with shorter length of stay (LOS) (6.2 vs 9.6 days), lower cost ($21, 674 vs $30, 380), and lower mortality (0 vs 3.3%); P < 0.05. Differences were noted in LOS and costs for all procedures, the differences were the greatest for hepatic resection (3.8 vs 8.4 days and $16, 770 vs $28, 589), intestinal resection/stoma closure (4.8 vs 7.6 days and $18, 391 vs $22, 239), and other abdominal procedures (5.0 vs 10.8 and $17, 713 vs $30, 900); P < 0.05. The differences were less for patients undergoing procedures for which postoperative pathways were already in place such as pancreatic (9 vs 10.8 days and $30, 524 vs $34, 291) and colorectal (5.3 vs 6.5 days and $20, 733 vs $25, 150) surgeries. P > 0.05. An ERAS program can be instituted by an individual surgeon with the benefits of decreased LOS, cost, and mortality.